EXPERIMENTAL STUDIES IN DETERMINATION OF BUBBLE EXTRACTOR FILTER’S FLUID CONDUCTIVITY - Karimov, Ikromali (International Journal of Psychosocial Rehabilitation, 2020)
In the article, fluid conductivity of bubble extractor’s glass fiber filter and it is operation to save the from mixing of nonsinking fluid droplets to the continuous fluid in the mixing zone of extractor are determined. Bubble extractor operates in liquid-liquid-gas system. In the results of theoretical researches formula for defining velocity of fluid outflow from the filter is recommended. By using that formula, fluid velocity that depends on coefficient resistance and flows through the filter surface and fluid displacement can be found. As the result, steady hydrodynamics of fluids movement in extractor’s mixing zone is provided. In order to determine the gas velocity by using the 1-formula several experimentations had been carried out. In continuous gas velocity heavy and light liquids which have different densities are selected and light liquid’s outflow velocity is determined experimentally. By using the recommended formula fluid outflow velocity is theoretically defined and compared with the experimental dates. With the help of computer processing of experimental dates had been made and values of correlation to the recommended formula had been entered. As the result of carried out experiments for determining fluid outflow velocity, 10-formula had been recommended. For selecting filter that value has the significant role in designing of apparatus.